Shear stress induced fabrication of dandelion-shaped lanthanide phosphate nanoparticles - D'Alonzo, N.; Eggers, P.; Eroglu, Ela; Raston, C. (CSIRO Publishing, 2017)
Lanthanide phosphate nanoparticles were co-precipitated under continuous flow in a vortex fluidic device in the presence of polyvinylpyrrolidone (PVP) of different molecular weights and at varying rotational speeds and tilt angles. Dandelionshaped lanthanide phosphate particles were produced at rotation speeds of 5000 rpm and 7000 rpm. In contrast, individual rods formed at 9000 rpm. Transition electron microscope images reveal changes in morphology of the dandelion-shaped nanoparticles with changes in the chain length of PVP or tilt angle of the tube of the vortex fluidic device. These morphological changes are likely to arise from different wrapping and aggregation of the nanoparticles induced by the PVP polymer under shear.